Whither Goest the Curriculum? - Rubin, Louis J. (Journal of Teacher Education)
The article presents an overview of the conflicting theories of education. This article aims to present several possible developments in the field of education with the aid of technological advancements. Among the educational predictions include contingency planning of information, the possibility that some of the projections will come out right than wrong, the chances that nobody can think of ways to prevent undesirable long-range development and the existence of short-run and long-run dimensions of social forecasting.